Implementation of a Factory-Based Learning Workshop Management Model to Improve Student Competence at SMK Negeri 3 Tondano - Lalompoh, Hartentus M.; Angmalisang, Harrychoon; Manggopa, Hiskia Kamang; Rompas, Parabelem Tinno Dolf (International Journal of Information Technology and Education, 2026)
This study aims to determine the effect of the Implementation of the Factory-Based Learning Workshop Management Model (Teaching Factory) to Improve Student Competence at SMK Negeri 3 Tondano. This study uses quantitative research with data collection techniques through questionnaire instruments. Based on the results of the analysis and discussion, the Implementation of the Factory-Based Learning Workshop Management Model (Teaching Factory) to Improve Student Competence by 98% while the rest is determined by other variables that are not studied in this study. So, the conclusion in this study is that there is a direct positive effect of the Implementation of the Factory-Based Learning Workshop Management Model (Teaching Factory) to Improve Student Competence at SMK Negeri 3 Tondano. This means that the Implementation of the Factory-Based Learning Workshop Management Model (Teaching Factory) can Improve Student Competence. Therefore, considering the influence of Factory-Based Learning (Teaching Factory) on Improving Student Competence, it is expected that all Vocational High Schools will implement Factory-Based Learning (Teaching Factory).